Alkaloid Profiling and Cholinesterase Inhibitory Potential of Crinum × amabile Donn. (Amaryllidaceae) Collected in Ecuador - Luciana R. Tallini; Angelo Carrasco; Karen Acosta León; Diego Vinueza; Jaume Bastida; Nora H. Oleas (Plants, 2021)
Natural products are one of the main sources for developing new drugs. The alkaloids obtained from the plant family Amaryllidaceae have interesting structures and biological activities, such as acetylcholinesterase inhibition potential, which is one of the mechanisms used for the palliative treatment of Alzheimer’s disease symptoms. Herein we report the alkaloidal profile of bulbs and leaves extracts of Crinum × amabile collected in Ecuador and their in vitro inhibitory activity on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) enzymes. Using Gas Chromatography coupled to Mass Spectrometry (GC-MS), we identified 12 Amaryllidaceae alkaloids out of 19 compounds detected in this species. The extracts from bulbs and leaves showed great inhibitory activity against AChE and BuChE, highlighting the potential of Amaryllidaceae family in the search of bioactive molecules.